Sindrom Marcus Gunn Kongenital Mengedipkan Rahang: Tinjauan Pustaka - Elvira; Abdi Sastra Gunanegara (Cermin Dunia Kedokteran, 2024)
Marcus-Gunn Jaw-winking syndrome is a rare congenital or acquired condition. This condition is characterized by upper eye lid elevation while opening or moving the jaw. In addition, it is accompanied by ptosis in the affected eye. Treatment options range from observation to surgery. Observation should be routinely done to evaluate any worsening symptoms. Surgery was performed for ocular misalignment and moderatesevere ptosis affecting visual function.